Bridging the Gap: Teaching Language Arts Concepts to English Language Learners (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
The number of English Language Learners continues to grow steadily each year. It is important that Language Arts concepts and strategies be implemented in the classroom to help these students increase their language development skills. This article explores why the understanding of Language Arts concepts are so critical to English Language Learners success in the classroom and provides some examples of strategies that can be utilized to strengthen their Language Arts skills. Overall, English Language Learners that have a strong understanding of Language Arts concepts are more likely to have success in a variety of learning content areas such as: mathematics, science, and social studies.
Keywords: English Language Learners; Literacy; Language